Determination of Trace Lead in Environmental Samples by Flow Injection and Hydride Generation Atomic Absorption Spectrometry - LIANG, JUNFENG; ZHANG, XIN; ZHOU, YUANQING; HU, QIUFEN (Asian Journal of Chemistry, 2010)
A new method for the determination of lead is proposed using flow injection and hydride generation atomic absorption spectrometry (HG-AAS). For this studies, (NH4)2S2O8 is used as the oxidizing agent, 100 μL of sample and 100 μL of 3.0 % (m/v) NaBH4 are simultaneously injected into two carrier streams, 0.5 % (m/v) tartaric acid and deionized water, respectively. A sampling rate of about 150 determinations per hour was achieved, requiring 15 mL of NaBH4 and a waste generation of 250 mL. The detection limit of 0.3 μg L-1 for Pb was achieved and the relative standard deviation of 2.1 % for 10 μg L-1 Pb was obtained. The method was shown to be satisfactory for determination of traces of Pb in food, water and soil samples.